Psychology and victims of the war in Croatia: Coping strategies of the family members of the missing persons - Knezović, Zvonimir (Array, 1996)
The data of the Government Commission for the Missing and Imprisoned Persons shows that in 1996 2688 persons were missing. The largest part of them (81,96%) have been missing since 1991. The survey conducted on the 145 family members of missing persons in the use of certain coping strategies showed that in most cases the fatalism have been used, followed by wishful thinking, problem solving, seeking social support and expression of emotions.